Detik-detik yang menentukan : jalan panjang Indonesia menuju demokrasi - Habibie, B. J. (Bacharuddin Jusuf), 1936- (Jakarta : THC Mandiri, 2006)
Account of Bacharuddin Jusuf Habibie, third president of the Republic of Indonesia, and his role in bringing Indonesia towards democracy
Keywords: Democracy -- Indoneisa -- History and criticism; Indonesia -- Democracy